Manajemen Risiko Pada Kegiatan Bunker Di Kapal Crew Boat Pt. Pan Maritime Wira Pawitra Jakarta: Risk Management In Bunker Activities On Crew Boat Pt. Pan Maritime Wira Pawitra Jakarta - Wenty Pratiwi Sugiyarti; Catur Septiawan G (MPI Press, 2021)
Introduction: Occupational accidents in the shipping industry still occur over the last 5 (five) years, one of the activities that have high potential for accidents that is at the time of refueling activities (Bunker). Objectives: The purpose of this research is to analyze the risk of refueling activities (Bunker) so it can easier to inform the risks and dangers that exist in the activities of refueling activities (Bunker) in 2017 on the vessel crew boat at PT. PWMP. Methods: This research qualitative with case study design, observation (site visit), interview (one person QHSE Manager, one person HSE Officer and three person engine crew), documentation and theory approach that support it based on OHSAS 18001: 2007 standard with semi quantitative method. Results: The result of research states that the highest danger on refueling activities (bunker) are fire and pollution of the marine environment. Conclusion: Suggestions for PT. PMWP to be more concerned in carrying out Safety Management System onboard to refueling activity (Bunker).